DIGITAL IMAGE WATERMARKING METHOD THROUGH PARTICLE SWARM OPTIMIZATION ALGORITHM USING DCT - Anu Jayalwal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Now a days there is increase in data exchange over digital media. As a result of that one multimedia data like audio, video, images transfer increases day by day. Watermarking is very famous now days due to security concern. There are many applications of watermarking with the help of which security can be increased in data. There are many areas where watermarking can be used such as copyright protection, fingerprint authentication, copy control etc. With the help of algorithms robustness and imperceptibility can be improved.